ANALISIS KEBERATAN, BANDING DAN PENGURANGAN (KBP) DALAM MENANGANI KEBERATAN WAJIB PAJAK UNTUK MEMPEROLEH KEADILAN DIKANWIL DIREKTORAT JENDRAL PAJAK (DJP) JAWA TIMUR III - Khusnul Fadila; Abdul Wahid Mahsuni; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The purpose of this study is to test and analyze empirically the meaning of the field of objection, appeal and deduction in dealing with the problem of objections to taxpayer facilities to obtain justice at the Regional Office of the Directorate General of Taxes East Java III. The population of the study is from taxpayers because of differences of opinion, misperceptions of regulations, negligence of taxpayers and the length of time for issuing objections to decrees. Based on the results of the study, it can provide a brief description that the objection to the tax case that has been carried out by Directorates General of Taxation East Java III. Objection Reviewers must investigate the formal requirements before then conduct an investigation based on material requirements such as summons of the Taxpayer, borrowing of books, records, data, and information owned by the Taxpayer relating to the content of the dispute. Not only that, the Objection Reviewer must also invite the Taxpayer to obtain acceptance whether the Taxpayer will accept or not from the research conducted by the Objection Reviewer before giving a decision for twelve (12) months. From this conclusion, there is a need for an evaluation the objections anticipate of new reviewers who previously served as Objection Reviewers who need longer time to resolve a Tax Objection case and the need to increase the number of objections researchers.Keywords: Taxpayer, Objection Decision Letter, Objection Reviewer.